Public Service Towards New Habit Adaptation In Kupang City - Umbu T.W. PARIANGU; Jacoba D. NIGA; Made Ingurah Demi YANA (Journal of Tourism Economics and Policy, 2023)
The Covid-19 pandemic which is still hitting various regions in the world, including Indonesia, has encouraged the government to immediately innovate and change policies and provide better public services for the benefit of society at large. besides that, because in the last two decades, the era of the industrial revolution 4.0 has entered, which demands the advancement of data and information systems, including in the public sector. This period gave the government a momentum to increase innovation to improve this sector. This is very complex so that and covers very broad aspects, this process experiences various obstacles and is encouraged to go through this towards adaptation to new habits or better known as the new normal era. This study uses a qualitative method with a descriptive-analytical method. This research shows a best practice in which the Kupang City Government (Pemkot) has carried out various innovations in public sector services such as the use of the SIMPEL application at the Civil Registry Population Service (DISDUKCAPIL) and SIPINTAR at the One-Stop Investment and Services Service (DPMPTSP) Kupang City as well as the QLUE application at the Kupang City Government. This innovation is able to provide a breakthrough in the process of providing public services which must still be carried out in the midst of a pandemic situation which necessitates ASN having to do Work from Home (WFH) and Work from Office (WFO). Even so, there are still several obstacles that need to be considered, especially by the Municipal Government of Kupang.